Fortification of calcium in Thai green curry paste - Weerawatanakorn, Monthana; Thi-on, Songwoot; Chittrakorn, Sasivimon; Ruttarattanamongkol, Khanitta (Food and Applied Bioscience Journal, 2017)
Green curry paste is the key ingredient of Thai chicken green curry which is the most popular curry in Thailand and widely consumed in all socioeconomic classes. The average calcium intake in Thailand is lower than the Thai Recommended Daily Intake (Thai RDI). Green curry paste appears to be the most suitable vehicle for calcium fortification to meet calcium requirements. The survey study was conducted to determine the mineral content of both green curry paste and Thai chicken curry. Six levels of fortified curry paste were studied including at 19%, 25%, 30%, 40%, 50% and 60% of Thai RDI (800 mg). Calcium lactate and calcium lactate gluconate were the calcium sources. Physico–chemical properties and sensory evaluation were used to evaluate the qualities. Storage stability was also evaluated. The results showed that Thai chicken curry contains low level calcium content (64 mg/serving) and the green curry paste also had a low level of calcium (15 mg/serving). Adding calcium significantly increased the lightness and slightly decreased the pH of the fortified green curry paste. The maximum level of calcium gluconate and lactate added were considered acceptable at 19% and 40% respectively by the sensory evaluation. After the 11 week storage period, approximately 2–3% calcium loss at 30°C storage compared to 1.4–1.6% calcium loss at 4°C storage. The temperature of storage had no effect on the color of the fortified products. The fortified products with both calcium lactate and gluconate were demonstrated to last for more than 11 weeks with standard qualities (compared to Thai community product standard No. 129/2546).